1999
DOI: 10.1175/1520-0469(1999)056<0374:ccewao>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Convectively Coupled Equatorial Waves: Analysis of Clouds and Temperature in the Wavenumber–Frequency Domain

Abstract: A wavenumber-frequency spectrum analysis is performed for all longitudes in the domain 15ЊS-15ЊN using a long (ϳ18 years) twice-daily record of satellite-observed outgoing longwave radiation (OLR), a good proxy for deep tropical convection. The broad nature of the spectrum is red in both zonal wavenumber and frequency. By removing an estimated background spectrum, numerous statistically significant spectral peaks are isolated. Some of the peaks correspond quite well to the dispersion relations of the equatoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

181
2,042
8
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,535 publications
(2,299 citation statements)
references
References 66 publications
181
2,042
8
8
Order By: Relevance
“…Such 'convective coupling' has been observed between convection and largescale equatorial waves in the tropics (Wheeler and Kiladis, 1999) and may be operating on the smaller scales here. Latent heat release from condensation and precipitation in the ascending part of the wave reduces the effective static stability, slowing the wave speed.…”
Section: Discussionmentioning
confidence: 99%
“…Such 'convective coupling' has been observed between convection and largescale equatorial waves in the tropics (Wheeler and Kiladis, 1999) and may be operating on the smaller scales here. Latent heat release from condensation and precipitation in the ascending part of the wave reduces the effective static stability, slowing the wave speed.…”
Section: Discussionmentioning
confidence: 99%
“…Liebmann and Hendon, 1990;Wheeler and Kiladis, 1999;Roundy and Frank, 2004;Yang et al, 2007aYang et al, , 2007bYang et al, , 2007c, substantially different values of N and l also yield reasonable dispersion solutions. Comparison of this dispersion relation with the shallow-water model of Matsuno (1966) reveals that the shallow-water model equivalent depth…”
Section: Solutionsmentioning
confidence: 99%
“…This dispersion is a consequence of relaxation of the hydrostatic approximation, and it is relevant only at a high zonal wave number. Wheeler and Kiladis (1999) and many others have demonstrated that observed convectively coupled Kelvin waves exhibit some dispersion especially between wave numbers 5 and 10, but Eq. (24) demonstrates that relaxing the hydrostatic approximation cannot explain this observed behaviour.…”
Section: Kelvin Wavementioning
confidence: 99%
“…During the active phase of the MJO, strong winds along with high humidity throughout the troposphere support the development of deep convective cloud systems that can persist for several days. Capturing the differences in these convective processes between the active and suppressed phases of the MJO-in particular, their vertical heating profiles-is key in order for GCMs to simulate tropical variability, in which the MJO plays a major role alongside other convectively coupled equatorial waves (Wheeler and Kiladis, 1999).…”
Section: Introductionmentioning
confidence: 99%